Evaluation of the Current Situation of Shelterbelts in Gadambaliya Area, Gadarif State, Sudan - Mohammed, Moatesum Babiker; Yousif Abdalla, Yasir; Mohamed Elagab, Mutasim Ali (Gezira Journal of Agricultural Science, 2023)
Abstract This study was carried in Gedarif  State in Gadambaliya area. during  (2020-2021). The study was aimed to evaluate of current situation of shelterbelts in the study area. Population of the study was 360 respondents from agricultural schemes owners, forests and range employees. Sample of this study was 103 respondents represents 28.6% from the population. Data were collected through questionnaire, group discussion, field survey and formal and informal meetings as a primary data. On the other hand secondary data was used from different sources as references and papers. Data analysis was using Statistical Package for the Social Sciences (SSPS), through using descriptive statistics and chi square test in addition to the content analysis. The findings of the study were; the types of trees in shelterbelts was Acacia seyal   and  Acacia senegal and the more effected by illegal cutting, over grazing and bests was Acacia seyal . the study shows  that schemes owners perceived that the shelterbelts  as valuable resource, socially, economically and  environmentally. While chi square test found that; There was no significant differences between the two categories of the respondents (scheme owners and employees) in determination of the shelterbelts direction, in effects type of the shelterbelts and in presence of training program about shelterbelts. The study recommended farmers to adopt the act of 2002 which reveals that “10% of their scheme should be planted as a shelterbelt”. Efforts have to be exerted towards stopping illegal cutting and initiation of artificial rehabilitation in order to avoid deterioration of the shelterbelts. Shelterbelts protection and training programs should be directed to the rural communities. تقييم الوضع الراهن للأحزمة الشجرية بمشاريع الزراعة الآلية المطرية بمنطقة القدمبلية ، ولاية القضارف - السودان معتصم بابكر محمد 1 ، د. ياسر يوسف عبد الله 2 ود. معتصم علي محمد العجب 3 1/كلية علوم وتكنولوجيا الغابات   - جامعة الجزيرة – السودان 2/ كلية علوم الغابات والمراعي -  جامعة السودان للعلوم و التكنولوجيا- السودان. 3/ كلية العلوم الزراعية - جامعة الجزيرة – السودان الملخص اجريت هذه الدراسة بولاية القضارف منطقة القدمبلية خلال الفترة 2020-2021. وتهدف الدراسة لتقييم الوضع الراهن للأحزمة الشجرية.  ضم مجتمع الدراسة 360 من أصحاب المشاريع الزراعية ، وموظفي الغابات والمراعي . اشتملت عينة الدراسة على  103 مبحوث بنسبة 28.6٪. اعتمدت الدراسة على المعلومات الاولية التي جمعت عن طريق الاستبيان والزيارة الميدانية ومجموعات النقاش والمقابلات الرسمية وغير الرسمية اضافة للمصادر الثانوية من كتب ورسائل منشورة وغير منشورة. تم تحليل البيانات باستخدام  برنامج الحزم الإحصائية للعلوم الاجتماعية (SSPS) من خلال استخدام الإحصاء الوصفي  و مربع كاي  كما تم استخدام تحليل المضمون. اوضحت الدراسة أن الاحزمة الشجرية قد تدهورت بفعل القطع الجائر ، كما اوضحت الدراسة ان الانواع الشجرية المكونة للأحزمة الشجرية هي الطلح و الهشاب وان شجرة الطلح هي اكثر الانواع الشجرية تاثرا بالقطع الجائر لاستخدامها كحطب حريق  وفحم كما انها الاكثر تاثرا  بالآفات والامراض والرعي الجائر، كما اوضحت الدراسة ان أصحاب المشاريع الزراعية ينظرون للاحزمة الشجرية كموارد قيمة ذات فائدة كبيرة وتوفر كثير من الفوائد البيئية والاقتصادية والاجتماعية .  و قد أوضح تحليل مربع كاي أنه لا توجد فروق معنوية بين اصحاب المشاريع و الموظفين في تحديد اتجاه الحزام و  آثاره و البرامج التدريبية المقدمة لهم . توصي الدراسة بضرورة تبني المزارعين لقانون عام 2002 بالكامل والذي ينص على " وجوب غرس 10٪ من مساحة مشاريعهم كحزام شجري". بذل جهود لوقف القطع غير القانوني والبدء في إعادة التأهيل الصناعي من أجل تجنب تدهور الأحزمة الواقية. توفير بدائل حطب الوقود والفحم، كما لابد من تكثيف حماية الأحزمة الشجرية وبرامج التدريب الإرشادية المناسبة للمجتمع المحلي.           Keywords:- Current situation, Deterioration, Evaluation, Gedambalyia, Shelterbelts